Efektivitas Penggunaan Media Quizizz Terhadap Minat Belajar Siswa Dalam Pembelajaran Online Akuntansi - Indah Cahya Sagala (Departement of Mathematics Education, 2023)
Accounting is a subject that requires high understanding and concentration to analyze and answer various accounting questions, so it takes a high interest in studying accounting, but due to the emergence of the Covid 19 pandemic, learning activities are carried out online, so media or digital platforms are needed that can arouse students' interest in accounting subjects. This study aims to analyze the effectiveness of using Quizizz media on students' learning interest in accounting online learning. The method used in this study is the systematic literature review method by searching for the keywords